1970
DOI: 10.3329/bja.v8i2.7019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Preeclampsia on the Weight of the Placenta

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This study also reveals that mean number of areas of syncytial knot formation (26.76), cytotrophoblastic cell proliferation (21.52), area of fibrinoid necrosis(10.68), and hyalinised villi (9.46) were increased in case of pre-eclamptic women, compared to normal pregnancy which were (9.60), (7.16) (2.24) and (2.32) respectively 33. M. Akhlag,.…”
mentioning
confidence: 55%
“…This study also reveals that mean number of areas of syncytial knot formation (26.76), cytotrophoblastic cell proliferation (21.52), area of fibrinoid necrosis(10.68), and hyalinised villi (9.46) were increased in case of pre-eclamptic women, compared to normal pregnancy which were (9.60), (7.16) (2.24) and (2.32) respectively 33. M. Akhlag,.…”
mentioning
confidence: 55%
“…A study was conducted by Shah et al 23 ., 1985; and others (Cibil LA 24 , Teasdale 25 , Barua R 26 ., and Begum 27 ), they also observed reduced placental weight (390.82 gm) in Pre-eclamptic women in compared to normal pregnant women (496.56 gm). A study was conducted by Segupta Kishwara, Abu Sadat, Shamim Ara 28 and others, Department of Anatomy, Dhaka Medical College, 2010. They observed lower placental weight in pre-eclampsia compare to normal pregnancy .Many foreign studies have shown the effect of Hypertensive disorders of pregnancy on the placental weight and the overall status of the mother and the baby, they reported the moderate to severe reduction of placental weight in pre-eclampsia and eclampsia 29 .…”
Section: Discussionmentioning
confidence: 99%